Improving Educators' Creativity through Self-Efficacy and Training - Wahyu Syahrizal; Maimun; Yonoriadi (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
The purpose of this study was to determine the relationship between self-efficacy and training with the creativity of educators at Setukpa Lemdiklat Polri Sukabumi. The study population was 149 educators and a sample of 109 educators. Data collection for each variable studied using a questionnaire with a rating scale. Data analysis techniques using descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a positive and significant relationship between self-efficacy and creativity of teaching staff with a correlation coefficient ry. 1 = 0.358 and regression equation Ŷ = 64.494 + 0.627X1. The contribution of self-efficacy to the creativity of teaching staff is 12%, (b) There is a significant positive relationship between personality and creativity of teaching staff with a correlation coefficient ry. 2 = 0.435 and regression equation Ŷ = 59.594 + 0.632X2, The contribution of personality to the creativity of teaching staff is 18.2%, and (c) There is a significant positive relationship between self-efficacy and personality together with the creativity of teaching staff with correlation coefficient R = 0.456 and regression equation Ŷ = 79.552 + 0.682.X1 + 1.161.X2. The contribution of self-efficacy and personality together to the creativity of teaching staff is 19.3%.